Towards climate smart agriculture: lessons from a coffee × banana case. Experiences from research for policy support in Uganda - Kangire A; Asten, Piet J.A. van; Verhagen J; Koomen, I. (2011)
Coffee and banana production in Uganda will be affected by climate change. While rainfall quantity might not drastically alter, its distribution is expected to become more erratic. Furthermore, the average temperature is expected to increase by 2 °C in the next few decades. This will affect coffee producing areas, most notably the Arabica growing regions, in addition an increase in pest and disease incidence is expected. Climate change is strongly connected to development issues. Economies, like Uganda, that depend heavily on natural resource based production systems such as agriculture, forestry and fisheries will feel the effects most profoundly. Smart development moves are needed beyond the traditional isolated approaches to achieve adaptation, mitigation, and development objectives.